2003
DOI: 10.1095/biolreprod.102.009316
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin-Like Growth Factor Binding Protein-1 Promoter Activity by FKHR and HOXA10 in Primate Endometrial Cells1

Abstract: Insulin-like growth factor binding protein-1 (IGFBP-1) is abundantly expressed in the liver and decidualized endometrium. FKHR, a FOXO forkhead transcription factor, stimulates IGFBP-1 promoter activity in liver cells through the insulin response sequences (IRSs). HOXA10, a homeobox transcription factor, is important in the decidualization process. Here we show that FKHR and HOXA10 are expressed in baboon endometrium during the menstrual cycle and pregnancy. Levels are lowest during the follicular phase and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 48 publications
2
73
0
1
Order By: Relevance
“…The cooperative action of FOXO transcription factors in endometrial decidualization is not only restricted to C/EBPb. The homeobox (HOX) protein HOXA10 also follows similar patterns of expression to FOXO1 during different stages of the baboon menstrual cycle and pregnancy (Kim et al, 2003). HOX proteins are developmentally regulated transcription factors that are important for spatial identity and differentiation of tissues in the developing embryo.…”
Section: Ccaat/enhancer-binding Protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooperative action of FOXO transcription factors in endometrial decidualization is not only restricted to C/EBPb. The homeobox (HOX) protein HOXA10 also follows similar patterns of expression to FOXO1 during different stages of the baboon menstrual cycle and pregnancy (Kim et al, 2003). HOX proteins are developmentally regulated transcription factors that are important for spatial identity and differentiation of tissues in the developing embryo.…”
Section: Ccaat/enhancer-binding Protein Interactionsmentioning
confidence: 99%
“…HOXA10 null mutant mice exhibit infertility due to compromised endometrial decidualization during blastocyst implantation (Benson et al, 1996). Kim et al were able to demonstrate a direct in vitro association between HOXA10 and FOXO1 as well as cooperative transactivation of the insulin-like growth factor-binding protein-1 (IGFBP-1) promoter (Kim et al, 2003). During pregnancy IGFBP-1 is expressed in decidualized stromal cells where it is thought to play a role during blastocyst implantation (Giudice et al, 1993).…”
Section: Ccaat/enhancer-binding Protein Interactionsmentioning
confidence: 99%
“…Only the roles of the proximal promoter region and transcription factors in the regulation of IGFBP-1 expression have been reported so far (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…However, lack of HOX A7 and HOX A9 expression blocks Hox/Meis/Pbx-mediated enhancement of MLL oncogenesis, resulting in the retention of normal B-developmental features. Interestingly, HOX A5 and HOX A10 have been shown to interact with FKHR regulating IGFBP-1 expression, 42,43 providing a potential pathway leading from altered HOX gene expression to loss of stromal cell/growth factor dependency in MLL leukemia. As recent studies have indicated that mechanisms of HOX gene regulation differ between wild-type MLL and truncated MLL, 16 BLIN-3 is a useful model for examining the regulation and potential requirement for HOX gene expression in MLL-mediated oncogenesis during human B-cell development.…”
Section: Discussionmentioning
confidence: 99%